A study on some aspects of reconstruction of images by parallel beam back projection method. (1st January 2013) - Pande, Shaifali; Ghoshal, Dibyendu
Parallel beam back projection method has been used to reconstruct the images (collected from standard books or literature) which had been acquired by using energy source of various frequency bands in electromagnetic spectrum. The present study has included various images in positive as well as negative forms. Images of stellar objects, natural phenomena and normal objects has been analysed by varying the image resolution and entropy of the reconstructed images have been calculated for various number of projections. It has been observed that the number of projections becomes higher with the increase of image resolution for having the larger amount of entropy. The study has also indicated that the entropy achieved for the reconstructed image at first increases and then passes through a maximum followed by a decreasing nature with the increase of number of projections. Histogram equalisation studies have further been made on each reconstructed image to have an insight to the contrast of reconstructed images.